Influence of organism stimulation with bacterial lipopolysaccharide on the metabolism of the extracellular matrix of the heart of rats under conditions of experimental metabolic syndrome - O.Ye. Akimov; A.O. Mykytenko; V.O. Kostenko (Medičnì Perspektivi, 2024)
Until recently, the extracellular matrix was considered only a structural component of the organ, which performs exclusively the function of the framework. However, recent studies provide insight into a much broader role of extracellular matrix in metabolic homeostasis, the transmission of intra-organ and tissue signals. Metabolic syndrome and chronic infectious diseases can change the extracellular matrix’s structure in the heart. However, the combined effect of bacterial lipopolysaccharide and metabolic syndrome on extracellular matrix of the heart remains insufficiently elucidated at present. The purpose of this work is to establish the effect of organism stimulation with bacterial lipopolysaccharide on the concentration of different fractions of glycosaminoglycans, the intensity of collagenolysis and the content of sialic acids in the heart of rats under conditions of experimental metabolic syndrome. The study was conducted on 24 sexually mature rats of the “Wistar” line weighing 200-260 g. Animals were divided into 4 groups with 6 animals in each group: control, metabolic syndrome group, lipopolysaccharide injection group and combination of lipopolysaccharide injection and metabolic syndrome group. Metabolic syndrome was modelled by using 20% fructose solution as the only water source. Lipopolysaccharide of S. typhi was administered according to the scheme: the first week, 0.4 μg/kg 3 times intraperitoneally, then once a week 0.4 μg/kg throughout the experiment. Experiment lasted for 60 days. The concentration of glycosaminoglycans, their separate fractions, the content of free L-hydroxyproline and sialic acids was studied in 10% rat heart homogenate. The combined effect of stimulation of the organism with bacterial lipopolysaccharide and metabolic syndrome modeling led to an increase in the total concentration of glycosaminoglycans in the heart of rats by 73.46% compared to the control group. Under these conditions, the concentration of the heparin-heparan fraction of glycosaminoglycans in the heart of rats increased by 188.64% compared to the control group. The content of the keratan-dermatan fraction of glycosaminoglycans increased by 75.34%, and the chondroitin fraction of glycosaminoglycans increased by 17.63%. The concentration of free L-hydroxyproline increased by 167.23%. The content of sialic acids increased by 66.95%. Metabolic syndrome, stimulation of the organism with bacterial lipopolysaccharide and their combination lead to intensification of degradation of the extracellular matrix of the heart of rats due to increased collagenolysis, destruction of proteoglycans and glycoproteins.